Extração semi-automática de rodovia baseada em um par estéreo de imagens aéreas e em otimização por programação dinâmica no espaço-objeto - Dal Poz, Aluir Porfírio [UNESP]; Gallis, Rodrigo de Araujo; Custodio da Silva, Joao Fernando [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2010)
This article proposes a method for 3D road extraction from a stereopair of aerial images. The dynamic programming (DP) algorithm is used to carry out the optimization process in the object-space, instead of usually doing it in the image-space such as the DP traditional methodologies. This means that road centerlines are directly traced in the object-space, implying that a mathematical relationship is necessary to connect road points in object and image-space. This allows the integration of radiometric information from images into the associate mathematical road model. As the approach depends on an initial approximation of each road, it is necessary a few seed points to coarsely describe the road. Usually, the proposed method allows good results to be obtained, but large anomalies along the road can disturb its performance. Therefore, the method can be used for practical application, although it is expected some kind of local manual edition of the extracted road centerline.
Semiautomatic road extraction based on a stereopar of aerial images and object-space dynamic programming optimization
Keywords: Dynamic programming; road model; feature extraction; road extraction; aerial images